365 nights in Hollywood - Wurtzel, Sol; Marshall, George; Faye, Alice 1915-1998 (Winner Road, Independence, MO Distributed exclusively by Englewood Entertainment, 1998)
Down-on-his-luck film director Jimmie Dale takes a job at a fly-by-night acting school. He is drawn into the plans of the school's owner to bilk a wealthy young man out of the funds he has supplied to shoot a movie starring pretty student Alice Perkins. But Jimmie hopes to bilk the bilkers by actually completing the movie as ostensibly planned.
Screenplay by Willaim Conselman, Henry Johnson ; Choreographed by Sammy Lee ; Music and Lyrics by Sidney Clare.
Alice Faye, James Dunn, Frank Mitchell, John Bradford, John Bradford, Grant Michelle, Frank Melton, John Qualen.
VHS format.
In English.
Keywords: Musical films; Comedy films